A user-priorities-based strategy for three-phase intelligent recommendation and negotiating agents for cloud services - Muhamad Hariz Muhamad Adnan (Tanjung Malim, 2023)
A user-priorities-based strategy for three-phase intelligent recommendation and negotiating agents for cloud services by Muhamad Hariz Muhamad Adnan